Scaling up effective professional development: Toward successful adaptation through attention to underlying mechanisms. (August 2022) - Patfield, Sally; Gore, Jennifer; Harris, Jess
Abstract: Delivering effective professional development (PD) at scale necessitates a careful balance between program integrity and local adaptation. Drawing on qualitative case study data, this paper explores tensions in the implementation of a successful PD program, Quality Teaching Rounds, within two contrasting school communities in New South Wales, Australia. Using the theoretical distinction between ostensive and performative aspects of implementation, we demonstrate how even slight surface-level adaptations to the program can have profound consequences for teacher learning. We argue that scaling efforts must attend to the underlying mechanisms of effective PD, not just its design, if benefits are to be realised. Highlights: Uses in-depth case studies to examine the implementation of Quality Teaching Rounds professional development. Investigates both the ostensive and performative aspects of implementation. Slight changes to surface-level intervention design can have profound consequences for the effectiveness of teacher learning. Scaling efforts must attend to an intervention's underlying theories of teacher change, not just design elements.